2013
DOI: 10.1016/j.str.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

IcmQ in the Type 4b Secretion System Contains an NAD+ Binding Domain

Abstract: A Type4b secretion system (T4bSS) is required for Legionella growth in alveolar macrophages. IcmQ associates with IcmR, binds to membranes and has a critical role in the T4bSS. We have now solved a crystal structure of IcmR-IcmQ to further our understanding of this complex. This structure revealed an amphipathic four-helix bundle, formed by IcmR and the N-terminal domain of IcmQ, which is linked to a novel C-terminal domain of IcmQ (Qc) by a linker helix. The Qc domain has structural homology with ADP ribosylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
6
0
2
Order By: Relevance
“…S8, Supplementary Material online). The structure of full-length IcmQ in complex with IcmR revealed that the C-terminal domain of IcmQ contains a NAD + binding domain (Farelli et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S8, Supplementary Material online). The structure of full-length IcmQ in complex with IcmR revealed that the C-terminal domain of IcmQ contains a NAD + binding domain (Farelli et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…2013). An alignment of IcmR from different bacteria was used to define the essential residues of this IcmR NAD + domain (Farelli et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the structure of full-length IcmQ in complex with IcmR was solved, revealing that the C-terminal domain of IcmQ contains an NAD + binding module. The presence of this module suggests that the IcmR–IcmQ complex binds to membranes, where the NAD(+)-bound form of the complex might promote stabilizing interactions with, or modification of, a protein in the Dot/Icm machine (Farelli et al 2013). …”
Section: Function Structure and Diversification Of T4ass And T4bsssmentioning
confidence: 99%
“…These toxins, generally found in Gram‐positive pathogenic organisms, are known to misregulate host processes such as actin cytoskeleton and microtubule dynamics by post‐translationally modifying key host small GTPases . The toxin‐specific activity has not been reported for Legionella, however, the ADPRTs have been detected and a structure of a homolog, IcmQ, critical for T4BSS functionality, has been described . These reports confirm the presence of ADPRT domains in Legionella, however their specific function, especially of those associated with HD domains, remains to be investigated.…”
Section: Resultsmentioning
confidence: 86%